Security Framework for Cloud Based Medical Monitoring System - Meera Gandhi, G.; John Jasper, J.; Andrew, Emmanuel (Asian Journal of Engineering and Applied Technology, 2017)
Our proposed work helps in developing a framework for cloud based medical system emergency situations, in order to provide a better and feasible service .The main objective of our article is to reach out and help people who are without any access to medical attention or facilities, increase security and maintain regular monitoring of patients by means of which their life can be protected . A new system is designed in such a way that any person can consult a doctor at any time through a smart phone. As a precaution to this problem, bio medical sensors are employed for monitoring the patient’s health even in the presence and absence of a health care professional. In this article we are using sensors mainly to measure heart beat, blood pressure and temperature. The sensor values are updated in the server and are available for the doctors to check. Doctors can prescribe medicines and medical advices, which are sent via patient’s mobile phone. Various measures like Accuracy, Sensitivity and Specificity are concentrated to verify the performance of the devices employed in the cloud based medical system. Our monitoring system provides efficient and regular monitoring by intimating the doctors for further of treatment .To ensure the safety of patients record Rabin’s Algorithm is used for the encryption.